2017
DOI: 10.1007/s10571-017-0505-1
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Induces Phenotypic Modulation of Vascular Smooth Muscle Cells via AMPK/mTOR/ULK1-Mediated Autophagy

Abstract: Phenotypic modulation of vascular smooth muscle cells (VSMCs) is involved in the pathophysiological processes of the intracranial aneurysms (IAs). Although shear stress has been implicated in the proliferation, migration, and phenotypic conversion of VSMCs, the molecular mechanisms underlying these events are currently unknown. In this study, we investigated whether shear stress(SS)-induced VSMC phenotypic modulation was mediated by autophagy involved in adenosine monophosphate-activated protein kinase (AMPK)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Activation of mTOR/P70S6K is responsible for VSMC dedifferentiation and proliferation [52] . Shear stress activates mTOR signaling to induce phenotypic modulation of VSMCs [53] . Exogenous miR-761 delivery inhibits angiotensin II-induced VSMC proliferation by targeting mTOR [54] .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of mTOR/P70S6K is responsible for VSMC dedifferentiation and proliferation [52] . Shear stress activates mTOR signaling to induce phenotypic modulation of VSMCs [53] . Exogenous miR-761 delivery inhibits angiotensin II-induced VSMC proliferation by targeting mTOR [54] .…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic changes and eventual loss of the media layer contribute to aneurysm formation and rupture. Previous histological studies have demonstrated that normally contractile SMCs respond to environmental cues by undergoing phenotypic changes, causing them to manifest a pro-inflammatory, pro-remodeling, and dedifferentiated phenotype 5 8 . The pro-inflammatory phenotype is characterized by reduced levels of the contractile elements of SMCs, accompanied by increased levels of transcription factors involved in promoting inflammation, recruitment of reactive oxygen species, and matrix remodeling 9 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In response to endothelial cell dysfunction, VSMCs, the main components of the arterial vessel wall, undergo a phenotypic switch from a contractile phenotype to a synthetic phenotype that is essential for vascular remodeling 25 . This VSMC phenotypic modulation is regulated by autophagy, and a previous study reported that the expression of the autophagy marker Beclin 1 is increased in shear stress-induced VSMC phenotypic modulation 26 . Autophagy plays an essential role in maintaining cellular homeostasis in physiological conditions 27,28 and participates in various physiological cellular processes as well as some pathological processes.…”
Section: Discussionmentioning
confidence: 54%